The McGraw - Hill college handbook - Marius Richard (MC Graw Hill, 1994)
The fourth edition of this acclaimed handbook continues to offer both a comprehensive reference to stylistic principles and rules and an accessible guide to the full writing process. Written by two highly regarded writers both in academia and the popular press, the revision features interdisciplinary examples and exercises and provides coverage of special topics such as writing about literature, argumentation, business writing, and writing in-class essays. With the new edition comes an extensive new chapter on writing in the disciplines and expanded coverage of the research paper that includes sample papers in both MLA and APA formats. In addition, the first four chapters on the writing process now incorporate greater emphasis on the documented essay.